Parabens do not increase fluoride uptake by dental enamel - Vanessa Silva Tramontino (RGO: Revista Gaúcha de Odontologia, 2010)
Objective: To evaluate whether methylparaben and propylparaben, which present a similar chemical structure, increase fluoride uptake by demineralized dental enamel when present in buffered solutions. Methods: The study comprised an in vitro experiment using blocks of bovine dental enamel with artificial carious lesions. Enamel blocks were exposed to the following treatment (n=12): fluoride solution (200 ppm fluoride) - control; solution containing fluoride and 13 mM methylparaben; solution containing fluoride and 13 mM propylparaben in 35% propylene glycol; solution containing fluoride in 35% propylene glycol. All solutions were buffered (0.01 M cacodilate) and the pH was adjusted to 6.27. The blocks were exposed to the treatment solutions in the proportion of 2 ml per mm2 of exposed enamel area and fluoride formed was estimated after removing an enamel layer by acid etching. Fluoride extracted was determined by ion specific electrode and the amount of enamel removed was estimated by phosphorus analysis. ANOVA followed by Tukey’s test were used for statistical analysis, with significance level at 5%. Results: The dental blocks of treatment groups containing both parabens and the control group presented similar fluoride concentration in enamel and no statistical difference was observed among them (p>0.05). The dental blocks of treatment group containing fluoride and propylene glycol showed the lowest value of fluoride present in enamel, which was significantly different from the control and fluoride and methylparaben groups (p<0.05). Conclusion: Methyl and propylparaben in a buffered solution do not enhance fluoride uptake by demineralized dental enamel.